SEMIOTICS ANALYSIS IN READING SIGN OF A FILM - Dirgantara, Rasyid (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2024)
Abstract Film discussions cannot be separated from their functions as entertainment and educational media. Subsequently, film is influential for be concentrated as an examination object. Semiotics is one common method for film interpretation. This study centers around how semiotic hypothesis is applied or used to notice and decipher signs in films and its utilization to help individuals like understudies, addresses, and so forth, particularly the people who expect to develop their insight in humanities films, By gathering reference sources pertinent to movies and semiotics from diaries and books as information, the consequences of this writing concentrate on made sense of that movies can be deciphered by applying Barthes‟ semiotic hypothesis such that components in movies like scenes, plots, exchanges, characters, and so on were seen to show signifiers, meant and sign. The consequences of conversation likewise proposed that the semiotic methodology by and large considers or treats all peculiarities as signs that can address or make an importance through figuring out legends and undertones.